Transformation of Arabic Language Curriculum Design towards Institutional Development of IAIN Kediri - Sholihuddin, Ahmad; Nidak, Khoiru; Zuhriyah, Lailatul (LP. Ma'arif Janggan Magetan, 2024)
This article explores curriculum mapping, needs analysis, and Arabic learning curriculum design in accordance with the direction of IAIN Kediri's institutional development towards UIN Sheikh Wasil. Using a qualitative approach, the primary data is in the form of curriculum structure documents and learning tools, sources and teaching staff, and learning activities. The data were collected using documentation, interviews, and observation. The results show that the Arabic learning curriculum map at IAIN Kediri has shifted. Arabic learning needs can be aligned with the scientific core of each study program: either as an institutional subject encompassing all language skills and elements, or tailored to program‑specific disciplines (religious/language‑based or general). In religious programs, the curriculum emphasizes reading religious texts and complex grammatical structures to support comprehension of specialist subjects, whereas general programs employ religious texts with basic grammar for reading purposes, omitting speaking skills. This dual‑path model necessitates institutional coordination to develop a consensus‑based core curriculum and tailored modules. Future research should employ mixed‑methods designs to assess learning outcomes and instructional efficacy across religious versus general tracks, and longitudinally investigate the impact of skill‑element proportions on graduates’ academic and professional competencies.